Kewirausahaan Politik Walikota Surakarta dalam Upaya Pengembangan Sumber Daya Manusia: Studi Kasus Revitalisasi Kawasan Sains dan Teknologi Solo Technopark - Yusuf Abdillah, Purnanda (Universitas Brawijaya, 2023)
This study aims to capture the practice of political entrepreneurship in human resource development efforts undertaken by Surakarta Mayor Gibran Rakabuming Raka. This research is important for expanding studies in the field of Political Science related to the practice of political entrepreneurship in Indonesia, particularly at higher levels. Political entrepreneurship actions are carried out through the utilization of authority in the form of resource allocation by political actors to generate profits and create maximum public benefits. By borrowing the alertness and discovery branch of thought in the theory of political entrepreneurship developed by McCaffrey and Salerno (2011), this study seeks to analyze the actions of political actors in presenting public benefits through the revitalization policy of the Solo Technopark Science and Technology. This research was qualitative, using a case study method through data collection in the form of interviews, documentation, literature study, and observation. The results showed that the Mayor of Surakarta is sensitive in seeing global challenges and answering these challenges through a solution that is ultimately able to bring benefits to the people in Surakarta City. The findings of this study show one side of the characteristics, that the practice of political entrepreneurship carried out at a higher level is able to produce greater benefits and benefits for the community and also political actors.